Industrial attachment final report with IBM, Singapore - Zhang, Jian (2008)
This report summarized the projects completed during the Industrial Attachment with IBM Singapore, Asia Pacific Product Procurement Team 745 from Feb to July, 2004. These projects are under continuous improvement of this department.